Intelligent Manufacturing Systems in Concept of Digital Factory - Martin Krajcovic; Vladimir Bulej; Ivan Kuric; Alzbeta Sapietova (Communications - Scientific letters of the University of Zilina, 2013)
This paper deals with selected areas of concept of Zilina Intelligent Manufacturing System (ZIMS), which is developed by the Faculty of Mechanical Engineering in collaboration with CEIT and other faculties of the University of Zilina. Main research areas realized in the framework of ZIMS cover the basic processes in the entire product lifecycle from beginning to end (PLM – Product Lifecycle Management). In this paper two of these areas will be described – manufacturing system design using progressive digital technologies and utilization of automation and robotics in intelligent manufacturing systems.